PTStore: Lightweight Architectural Support for Page Table Isolation - Tan, Wende; Chen, Yangyu; Li, Yuan; Liu, Ying; Wu, Jianping; Ding, Yu; Zhang, Chao (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Page tables are critical data structures in kernels, serving as the trust base of most mitigation solutions. Their integrity is thus crucial but is often taken for granted. Existing page table protection solutions usually provide insufficient security guarantees, require heavy hardware, or introduce high overheads. In this paper, we present a novel lightweight hardware-software co-design solution, PTStore, consisting of a secure region storing page tables and tokens verifying page table pointers. Evaluation results on FPGA-based prototypes show that PTStore only introduces <0.92% hardware overheads and <0.86% performance overheads, but provides strong security guarantees, showing that PTStore is efficient and effective.